Kreatifitas Merangkai Bunga Kering bagi Ibu-Ibu PKK Perumahan Bungo Bumi Indah Kelurahan Bungo Pasang Kecamatan Koto Tangah Kota Padang - Wati Wati; Deltri Apriyeni; Meri Rahmania; Nazirwan Nazirwan; Indro Saputro (Warta Pengabdian Andalas, 2020)
Based on the development program, the goal to be achieved is to shape individuals and communities to become independent. This independence includes the independence of thinking, acting, and controlling what they do. From observations made, there are PKK members who only act as housewives. Though they can earn money to support their family income. As a solution, they need to get proper training conducted by the local government, service programs, or certain other institutions. In line with this PKM activity, there will be training and fostering creativity for PKK members through the use of dried grains into various dried flower creations. This activity was began with communicate by local PKK management. The presentation of the material was done by the method of lectures and discussions. Furthermore, training and practice directly make dried flowers with materials that have been prepared by the service team. To motivate participants to be more creative and uplifting, the dedication team presented a ready-made example. It hopes that participants will gain useful skills and eventually become creative and skilled human beings to increase family income.